(untitled) (Research, Society and Development, 2021)
Traditional preclinical radiology training in humans is contraindicated as exposure to unnecessary ionizing radiation can be harmful to health. Currently, there are methods developed for teaching X-rays, such as the use models, artificial skulls or even virtual reality. However, these techniques have limitations, such as not having anatomical repair points and limitation of the lips and jugal mucosa, not simulating the proper positioning of the patient and the X-ray machine, and not adding knowledge of radiographic interpretation and high cost. Thus, the aim of this study was to develop a practical preclinical dental radiology teaching method by means of a new device with characteristics of the oral cavity and teeth that can be connected to a patient phantom, enabling the use of positioners, positioning of x-ray beams, as well as the interpretation of characteristics and low cost. To make the device, it was used a commercial dental model, added with features such as teeth with pulp camera, bone trabeculate, endodontically treated tooth, restorations, fixed prosthesis, implants, root, cysts and tooth absence. The device can be connected to a patient phantom in order to simulate working positions, use of radiographic positioners, patient positioning and x-ray beams. It is concluded that it is possible to mimic the oral cavity at low cost so that students can acquire knowledge of radiology prior to clinical practice in patients.